Protección igualitaria en un mundo de consumidores heterogéneos: el análisis económico del derecho del consumidor en acción - Rodríguez García, Gustavo (2023)
Consumers have different preferences, needs and limitations. Notwithstanding this unquestionable fact, consumer protection systems tend to bet blindly on equal protection schemes. Even more seriously, many egalitarian schemes operate as mandatory schemes. In this paper, it is argued that such schemes severely injure the principle of consumer sovereignty and injure the consumer since they move away from the spontaneous market process and replace it with rigid designs that inevitably affect those consumers whose preferences or possibilities move away from the rule laid down by legislation.